Method for preparing nitrogen-containing graphene by taking chitosan as raw material

By using chitosan as a raw material, combined with spin coating technology and annealing and carbonization treatment under nitrogen protection, the existing graphene preparation methods are solved, and the high cost and environmental pollution of the existing graphene preparation methods are achieved, and the efficient and environmentally friendly nitrogen-containing graphene preparation is achieved, which improves the performance of graphene.

CN119706816AInactive Publication Date: 2025-03-28JIANGSU CHITIN BIOTECH CO LTD +1

Patent Information

Application Number
CN202510078318.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing graphene preparation methods have problems such as high cost, time-consuming, and environmental pollution, and the crystallinity of the graphene produced is insufficient, which affects the conductivity.

Method used

Chitosan is used as the raw material, and evenly covered on the quartz substrate by spin coating technology, annealing and carbonization are performed under nitrogen protection, and then activated to obtain nitrogen-containing graphene products.

Benefits of technology

The preparation of large-area, high-quality, single-layer to multi-layer nitrogen-doped graphene has been achieved, which reduces production costs and avoids environmental pollution, and the conductive and catalytic performance of graphene has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706816A_ABST
    Figure CN119706816A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing nitrogen-containing graphene by taking chitosan as a raw material, and belongs to the technical field of nitrogen-containing graphene. The preparation method comprises the following steps: uniformly coating a mixed solution of chitosan and acetic acid on the surface of a quartz base material by adopting a spin coating technology, then slowly heating and annealing the base material coated with the mixed solution in a nitrogen protection environment, after the temperature is naturally reduced to room temperature, lightly scraping off a chitosan film from the base material, placing the base material in a nitrogen atmosphere again, and carrying out two-step carbonization to obtain the chitosan / acetic acid composite material. After carbonization is completed, naturally cooling to room temperature to obtain a pre-carbonized product; and uniformly mixing the obtained pre-carbonized product with a regulating agglomeration agent according to a mass ratio of 1: 1. Then, two-step activation treatment is carried out, after activation is completed, after the system is cooled to the room temperature, a product is subjected to aftertreatment and drying, and a nitrogen-containing graphene product is obtained. Chitosan is spin-coated to prepare a film before high-temperature carbonization, and then an annealing reaction is carried out for a period of time. The conformation of the polymer fiber treated by the step is loose, and formation of a graphene layer is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nitrogen-containing graphene, and in particular to a method for preparing nitrogen-containing graphene using chitosan as a raw material. Background Art

[0002] As a two-dimensional material tightly woven from a single layer of carbon atoms, graphene shines in many fields such as electrode materials and electronic component manufacturing due to its excellent electrical conductivity, thermal conductivity, high light transmittance and excellent specific surface area. Compared with its pure form, nitrogen-containing graphene not only adjusts the energy gap of graphene and achieves precise control of electrical properties through the clever doping of nitrogen, but also greatly enriches the active sites on its surface. These sites are like micro-factories of catalysts, accelerating the chemical reaction process and significantly improving the catalytic efficiency of graphene. In the commercial preparation path of graphene, chemical vapor deposition (CVD) and Hummers method occupy an important position.

[0003] When graphene is prepared by CVD, a carbon-containing precursor is usually used to decompose at high temperature on the surface of a metal substrate (such as copper, nickel, platinum, etc.) to generate a graphene film. This method is known for its high repeatability and adaptability to industrial production, but it still faces challenges such as high cost, long time consumption, disposable metal substrates, and fragility of film transfer.

[0004] On the other hand, Hummers's rule cleverly uses the oxidation system of concentrated sulfuric acid and potassium permanganate, supplemented by aniline as a nitrogen source, to transform graphite, and then reduce it to obtain nitrogen-containing graphene. However, the crystallinity of graphene produced by this method is slightly insufficient, and the residual oxygen functional groups may have a subtle effect on its conductive properties.

[0005] It is worth noting that both of the above methods have an impact on the environment to varying degrees. The consumption and unsustainability of the metal substrate in the CVD method and the large amount of acidic wastewater discharged in the Hummers method pose a potential threat to the environment and indirectly increase production costs. Therefore, exploring and implementing green and environmentally friendly production processes has become the key to reducing the production cost of nitrogen-containing graphene and promoting the sustainable development of its industry. Therefore, deepening the exploration of green and environmentally friendly production processes can lead the nitrogen-containing graphene industry to a more brilliant future. Summary of the invention

[0006] The purpose of the present application is to provide a method for preparing nitrogen-containing graphene using chitosan as a raw material. The method is green, environmentally friendly, and can reduce the production cost of nitrogen-containing graphene.

[0007] To achieve the above object, the present application provides a method for preparing nitrogen-containing graphene using chitosan as a raw material, comprising the following steps:

[0008] Step 1: dissolve chitosan in an acetic acid solution with a concentration of 3%-5% to form a mixed solution, and then use a spin coating technique to evenly coat the mixed solution on the surface of a quartz substrate. Subsequently, under a nitrogen protection environment, the substrate coated with the mixed solution is heated to 200° C. and annealed at this temperature for 2 hours to promote the initial solidification of the chitosan. After the annealing process, the conformation of the polymer fiber is relaxed, which is beneficial to the formation of a graphene layer in the subsequent carbonization step, and this conformational relaxation is more effective in a uniform coating. After the temperature naturally drops to room temperature, the chitosan film with nanometer size and subnanometer roughness is gently scraped off from the substrate;

[0009] Step 2: The chitosan film obtained in step 1 is placed in a nitrogen atmosphere again for two-step carbonization. After the carbonization is completed, it is naturally cooled to room temperature to obtain a pre-carbonized product;

[0010] Step 3: Evenly mix the pre-carbonized product obtained in step 2 with the regulating agglomeration agent in a mass ratio of 1:1, and then perform a two-step activation treatment. After the activation is completed, wait for the system to cool to room temperature, post-treat the product, and dry it to obtain a nitrogen-containing graphene product.

[0011] Preferably, in step 2, the two-step carbonization process is as follows: first, the temperature is raised to 400-500°C and maintained for 1 to 2 hours for preliminary carbonization, and then the temperature is continued to be raised to 800°C and maintained at this temperature for 1 to 2 hours to complete the deep carbonization process.

[0012] Preferably, in step three, the regulating agglomeration agent is one or more of KOH, Zn(NO3)2, and ZnSO4.

[0013] Preferably, in step three, the two-step activation treatment is as follows: under nitrogen protection, the mixture is heated to 500-800°C, kept warm for 1 to 2 hours, and then continued to heat to 900-1100°C and kept warm for 0.5 to 1 hour.

[0014] Preferably, in step three, the specific steps of post-treatment are: first, washing with deionized water until the solution is neutral to remove impurities; then, washing the sample 3 times with anhydrous ethanol; finally, drying the sample in an oven at 60° C. to obtain a nitrogen-containing graphene product.

[0015] Preferably, in step 1, the heating rate of the substrate coated with the mixed solution is 5° C. / min.

[0016] Preferably, in step 2 and step 3, the heating rate of preliminary carbonization and deep carbonization is 5°C / min, and the cooling rate is 10°C / min.

[0017] The present application also provides a nitrogen-containing graphene prepared according to the above method.

[0018] Therefore, the present application provides a method for preparing nitrogen-containing graphene using chitosan as a raw material, which has the following characteristics:

[0019] Beneficial effects:

[0020] 1. The present invention innovatively proposes a green and efficient method for preparing large-area, high-quality, single-layer to multi-layer nitrogen-doped graphene on a wide range of material surfaces, including but not limited to glass, silicon and quartz. This method is not only low-cost, but also follows the principles of safety and environmental protection throughout the process, completely abandoning the catalysts, concentrated sulfuric acid and other harmful substances required in traditional processes, and also effectively avoiding the use of metals such as nickel and copper that have a heavy environmental burden.

[0021] 2. The core of the present invention is to efficiently utilize the natural nitrogen-containing chitosan, which is abundant in nature, as a nitrogen source. Through a unique process design, the precise doping of nitrogen in the graphene structure is achieved, which not only retains the original excellent properties of graphene, but also gives it new electrical, catalytic and other properties. This process not only simplifies the preparation process and improves production efficiency, but also greatly reduces the negative impact on the environment and realizes the efficient recycling of resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the Raman spectrum of the nitrogen-containing graphene product obtained in Example 1;

[0023] Figure 2 This is a SEM image of the nitrogen-containing graphene product obtained in Example 1;

[0024] Figure 3 This is the Raman spectrum of the nitrogen-containing graphene product obtained in Comparative Example 1;

[0025] Figure 4 This is the Raman spectrum of the nitrogen-containing graphene product obtained in Comparative Example 2;

[0026] Figure 5 This is the Raman spectrum of the nitrogen-containing graphene product obtained in Comparative Example 3. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further illustrated by the following examples.

[0028] Example 1

[0029] Step 1: Dissolve chitosan in 5% acetic acid solution, ensure that it is completely dissolved, and then evenly cover it on a quartz or glass substrate by spin coating. Subsequently, in a nitrogen protection environment, heat the substrate with chitosan spun on it to 200°C at a heating rate of 5°C / min and keep it at this temperature for 2 hours to promote the initial solidification of chitosan. After that, cool it naturally to room temperature, and use an appropriate method to peel the chitosan film from the substrate for later use.

[0030] Step 2: Take an appropriate amount of the previously prepared chitosan film and place it in a corundum porcelain boat, and then put it into a tubular furnace in a nitrogen atmosphere again. Raise the furnace temperature to 500°C at a heating rate of 5°C / min and keep it warm for 1 hour for preliminary carbonization. Then, continue to heat it to 800°C at the same heating rate and keep it warm for 2 hours to complete the deep carbonization process. After the carbonization is completed, control the cooling rate to 10°C / min until the furnace temperature drops to room temperature. At this time, the graphene pre-carbonized product is obtained.

[0031] Step 3: In order to further improve the performance of the pre-carbonized product, weigh the graphene pre-carbonized sample and 2 times the mass of KOH, grind and mix them thoroughly in a mortar, and then place them in a corundum porcelain boat. Under nitrogen protection, place the mixture in a tubular furnace, heat it to 500°C at a heating rate of 5°C / min, and keep it warm for 1 hour for preliminary activation. Subsequently, continue to heat it to 1100°C at a heating rate of 5°C / min and keep it warm for 30 minutes to achieve activation. After activation is completed, the cooling rate is also controlled to 10°C / min, and the sample is taken out after it drops to room temperature.

[0032] The sample was post-processed: first, it was repeatedly washed with deionized water until the solution was neutral to remove residual KOH and other impurities; then, the sample was washed three times with anhydrous ethanol for further purification. Finally, the cleaned sample was placed in an oven at 60°C for drying to obtain the final nitrogen-containing graphene product.

[0033] Figure 1 The Raman spectrum of the sample is shown. Figure 2 The SEM image of the sample is shown, from which it can be clearly seen that the D / G ratio of the sample is 0.95. At the same time, the 2D peak is clearly visible and the relative height is the highest in the case (2D / G ratio is 0.49), which further confirms that the prepared nitrogen-containing graphene has a good crystal structure and high quality. Different from the other groups that did not perform step one chitosan spin coating.

[0034] Comparative Example 1

[0035] Step 1: Dissolve chitosan in 5% acetic acid solution, ensure that it is completely dissolved, and then evenly cover it on a quartz or glass substrate by spin coating. Subsequently, in a nitrogen protection environment, heat the substrate with chitosan spun on it to 200°C at a heating rate of 5°C / min and keep it at this temperature for 2 hours to promote the initial solidification of chitosan. After that, cool it naturally to room temperature, and use an appropriate method to peel the chitosan film from the substrate for later use.

[0036] Step 2: Take an appropriate amount of the previously prepared chitosan film and place it in a corundum porcelain boat, and then put it into a tubular furnace in a nitrogen atmosphere again. Raise the furnace temperature to 500°C at a heating rate of 5°C / min and keep it warm for 1 hour for preliminary carbonization. Then, continue to heat it to 800°C at the same heating rate and keep it warm for 2 hours to complete the deep carbonization process. After the carbonization is completed, control the cooling rate to 10°C / min until the furnace temperature drops to room temperature. At this time, the graphene pre-carbonized product is obtained.

[0037] Step 3: Weigh the graphene pre-carbonized sample and an equal amount of KOH, grind and mix them thoroughly in a mortar, and place them in a corundum boat. Under nitrogen protection, place the mixture in a tubular furnace, heat it to 500°C at a heating rate of 5°C / min, and keep it warm for 1 hour for preliminary activation. Subsequently, continue to heat it to 1100°C at a heating rate of 5°C / min and keep it warm for 30 minutes to achieve activation. After activation is completed, the cooling rate is also controlled to 10°C / min, and the sample is taken out after it drops to room temperature.

[0038] The sample was post-processed: first, it was repeatedly washed with deionized water until the solution was neutral to remove residual KOH and other impurities; then, the sample was washed three times with anhydrous ethanol for further purification. Finally, the cleaned sample was placed in an oven at 60°C for drying to obtain the final nitrogen-containing graphene product.

[0039] Figure 3 The Raman spectrum of the sample is shown, from which it can be clearly seen that the D / G ratio of the sample is 0.93. At the same time, the 2D peak is clearly visible (2D / G ratio is 0.39), and compared with the nitrogen-containing graphene product in Example 1 above, the 2D / G ratio is relatively low, indicating that the amount of KOH added is small, and the graphene content produced is relatively small; vice versa.

[0040] Comparative Example 2

[0041] Step 1: Take an appropriate amount of chitosan and place it in a corundum porcelain boat, and then put it into a tubular furnace in a nitrogen atmosphere. Raise the furnace temperature to 500°C at a heating rate of 5°C / min and keep it warm for 1 hour for preliminary carbonization. Then, continue to heat it to 800°C at a heating rate of 5°C / min and keep it warm for 2 hours to complete the deep carbonization process. After the carbonization is completed, control the cooling rate to 10°C / min until the furnace temperature drops to room temperature. At this time, the graphene pre-carbonized product is obtained.

[0042] Step 2: Weigh the graphene pre-carbonized sample and an equal amount of KOH, grind and mix them thoroughly in a mortar, and place them in a corundum boat. Under nitrogen protection, place the mixture in a tubular furnace, heat it to 500°C at a heating rate of 5°C / min, and keep it warm for 1 hour for preliminary activation. Subsequently, continue to heat it to 1100°C at a heating rate of 5°C / min and keep it warm for 30 minutes to achieve activation. After activation is completed, the cooling rate is also controlled to 10°C / min, and the sample is taken out after it drops to room temperature.

[0043] The sample was post-processed: first, it was repeatedly washed with deionized water until the solution was neutral to remove residual KOH and other impurities; then, the sample was washed three times with anhydrous ethanol for further purification. Finally, the cleaned sample was placed in an oven at 60°C for drying to obtain the final nitrogen-containing graphene product.

[0044] Figure 4 The Raman spectrum of the sample is shown, and it can be clearly seen from the figure that the D / G ratio of the sample is 0.94. At the same time, the 2D peak is clearly visible (the 2D / G ratio is 0.21). Compared with the nitrogen-containing graphene product in the above-mentioned comparative example 1, the 2D / G ratio is relatively low, indicating that the graphene content produced by preparing the graphene pre-carbonized sample by evenly covering chitosan on a quartz or glass substrate by spin coating technology is relatively high; while the graphene content produced by directly using chitosan as a graphene pre-carbonized sample is relatively low.

[0045] Comparative Example 3

[0046] Step 1: Dissolve chitosan in 5% acetic acid solution, ensure that it is completely dissolved, and then evenly cover it on a quartz or glass substrate by spin coating. Subsequently, in a nitrogen protection environment, heat the substrate with chitosan spun on it to 200°C at a heating rate of 5°C / min and keep it at this temperature for 2 hours to promote the initial solidification of chitosan. After that, cool it naturally to room temperature, and use an appropriate method to peel the chitosan film from the substrate for later use.

[0047] Step 2: Take an appropriate amount of chitosan and place it in a corundum porcelain boat, and then put it into a tubular furnace in a nitrogen atmosphere again. Raise the furnace temperature to 500°C at a heating rate of 5°C / min and keep it warm for 1 hour for preliminary carbonization. Then, continue to heat it to 800°C at a heating rate of 5°C / min and keep it warm for 2 hours to complete the deep carbonization process. After the carbonization is completed, control the cooling rate to 10°C / min until the furnace temperature drops to room temperature. At this time, the graphene pre-carbonized product is obtained.

[0048] Step 3: Weigh the graphene pre-carbonized sample and an equal mass of Zn(NO3)2 and KOH, grind and mix them thoroughly in a mortar, and place them in a corundum boat. Under nitrogen protection, place the mixture in a tubular furnace, heat it to 500°C at a heating rate of 5°C / min, and keep it warm for 1 hour for preliminary activation. Subsequently, continue to heat it to 1100°C at a heating rate of 5°C / min and keep it warm for 30 minutes to achieve activation. After activation is completed, the cooling rate is also controlled to 10°C / min, and the sample is taken out after it cools to room temperature.

[0049] The sample was post-processed: first, it was repeatedly washed with deionized water until the solution was neutral to remove residual Zn(NO3)2 and other impurities; then, the sample was washed three times with anhydrous ethanol for further purification. Finally, the cleaned sample was placed in an oven at 60°C to dry to obtain the final nitrogen-containing graphene product.

[0050] Figure 5 The Raman spectrum of the sample is shown, from which it can be clearly seen that the D / G ratio of the sample is 0.95. At the same time, the 2D peak is clearly visible (2D / G ratio is 0.28). Compared with the nitrogen-containing graphene products in Comparative Examples 1 and 2, the 2D / G ratio is relatively low, indicating that the addition of Zn(NO3)2 is not conducive to producing a high graphene content; nitrate NO3 - It has a certain degree of expansion, which destroys the structure of ordered graphene.

[0051] Therefore, the present application provides a method for preparing nitrogen-containing graphene using chitosan as a raw material. Different from other heat treatment methods, the present invention spin-coats chitosan before high-temperature carbonization and then performs an annealing reaction for a period of time. After this step, the conformation of the polymer fiber is relaxed, which is conducive to the formation of a graphene layer and can improve the performance of the graphene product.

[0052] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.

[0053] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing nitrogen-containing graphene using chitosan as raw material, characterized in that: The following steps are involved: Step 1: dissolving chitosan in an acetic acid solution with a concentration of 3-5% to form a mixed solution, and then using a spin coating technique to evenly coat the mixed solution on the surface of a quartz substrate. Subsequently, under a nitrogen protection environment, heating the substrate coated with the mixed solution to 200° C. and annealing at this temperature for 2 hours, and after the temperature naturally drops to room temperature, scraping off the chitosan film with nanometer size and sub-nanometer roughness from the substrate; Step 2: The chitosan film obtained in step 1 is placed in a nitrogen atmosphere again for two-step carbonization. After the carbonization is completed, it is naturally cooled to room temperature to obtain a pre-carbonized product; Step 3: Evenly mix the pre-carbonized product obtained in step 2 with the regulating agglomeration agent in a mass ratio of 1:1 or 2:1, and then perform a two-step activation treatment. After the activation is completed, wait for the system to cool to room temperature, post-treat the product, and dry it to obtain a nitrogen-containing graphene product.

2. A method for preparing nitrogen-containing graphene using chitosan as raw material according to claim 1, characterized in that: In step 2, the two-step carbonization process is as follows: first, the temperature is raised to 400-500°C and maintained for 1 to 2 hours for preliminary carbonization, and then the temperature is continued to be raised to 800°C and maintained at this temperature for 1 to 2 hours to complete the deep carbonization process.

3. A method for preparing nitrogen-containing graphene using chitosan as raw material according to claim 1, characterized in that: In step three, the agglomerating agent is regulated to be one or more of KOH, Zn(NO3)2, and ZnSO4.

4. A method for preparing nitrogen-containing graphene using chitosan as raw material according to claim 1, characterized in that: In step three, the two-step activation treatment is as follows: under nitrogen protection, the mixture is heated to 500-800°C, kept warm for 1 to 2 hours, and then continued to heat to 900-1100°C and kept warm for 0.5 to 1 hour.

5. A method for preparing nitrogen-containing graphene using chitosan as raw material according to claim 1, characterized in that: In step three, the specific steps of post-treatment are: first, wash with deionized water until the solution is neutral to remove impurities; then, wash the sample three times with anhydrous ethanol, and finally, place the sample in an oven at 60°C to dry to obtain a nitrogen-containing graphene product.

6. A method for preparing nitrogen-containing graphene using chitosan as raw material according to claim 1, characterized in that: In step 1, the heating rate of the substrate coated with the mixed solution is 5° C. / min.

7. A method for preparing nitrogen-containing graphene using chitosan as raw material according to claim 1, characterized in that: In step 2 and step 3, the heating rate of preliminary carbonization and deep carbonization is 5°C / min, and the cooling rate is 10°C / min.

8. Nitrogen-containing graphene obtained by the method for preparing nitrogen-containing graphene using chitosan as raw material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing nitrogenous hierarchical pore three-dimensional graphene by using chitosan

    CN103922328A

  • Nitrogen-doped ordered porous high-conductivity graphene fiber, preparation method and application thereof

    CN107275116A

  • Method for preparing nitrogen-containing graphene material from chitosan

    CN107840322A

  • Preparation and application of 3D nitrogen-sulfur-doped graphene / self-assembled polysaccharide composite material

    CN110514717A

  • Preparation method of modified nitrogen-doped carbon aerogel

    CN111389358A

Cited By

  • Method for preparing nitrogen-containing graphene by taking chitosan as raw material and nitrogen-containing graphene device

    CN121536915A

  • A method for preparing nitrogen-containing graphene using chitosan as a raw material and a nitrogen-containing graphene device.

    CN121536915B